"The Indian ocean and its Islands: strategic, scientific and historical perspectives" - "Chandra, Satish" (New Delhi, 1993)
Many studies exist which focus on the Indian Ocean, but none have been written examining the importance of the numerous islands found there. In this original volume, a team of naval officers and scholars discusses four basic themes relating to this area of the world: strategic, legal, exploitation of resources, and maritime traditions. While the contributors assess the scientific and developmental aspects of the islands in specific relation to India, these issues have a broad application to the problems facing all littoral countries. "A highly readable book; it is a virtual encyclopaedia on the Indian Ocean and its islands."
Keywords: Indian ocean region-Politics and government